A Nose for Death: Integrating Trophic and Informational Networks for Conservation and Management - Jones, Menna E.; Apfelbach, Raimund; Banks, Peter B.; Cameron, Elissa Z.; Dickman, Chris R.; Frank, Anke; McLean, Stuart; McGregor, Iain S.; Müller-Schwarze, Dietland; Parsons, Michael H.; Sparrow, Elisa; Blumstein, Daniel T. (Frontiers in Ecology and Evolution, 2016)
Non-lethal management of wildlife, both ‘problem wildlife’ and pest species, to protect crops and threatened species is becoming increasingly important as non-human animals and humans come into closer proximity. A particularly promising approach is to apply predator scents to manipulate the cost/benefit ratio that influences the behavioral decisions made by prey and other predators about where to forage or rest. However, such olfactory manipulations are not always successful. Using insights from size-structured food webs, we develop a novel integrative model of the information that animals acquire from eavesdropping on predator and conspecific scents. We show how animals can use the information content in predator scents to derive knowledge of other predators and competitors and thus influence their decision to stay in or leave an area. This model framework clarifies how predator scents can influence all trophic levels, from interference competition directed at smaller predators, to predation and herbivory, and exploits direct and indirect pathways to promote landscapes of fear that influence spatial and temporal patch use in target animals. We illustrate how the application of this conceptual model can focus future research to enhance the use of predator scent-based deterrents in conservation and management. This integrated model shows great promise for addressing wildlife management concerns and for eventually improving the success and efficacy of traditional management techniques.